1. x + y = 2
2. y = 2x - 13
Rewriting 2. as:
3. 2x - y = 13
Adding 1 & 3 gives:
4. 3x = 15
x = 5
Substituting x = 5 into 1. gives:
5 + y = 2
y = 2 - 5
y = -3
Checking values by substituting x = 5 and y = -3 into 2 gives:
-3 = (2 * 5) - 13
-3 = 10 - 13
-3 = -3
Therefore x = 5 and y = -3.
It is (-1, 3).
143542make the variables X plus Y plus Zthe solution is X*Y,X*Z, then (X+Z)*Y flipped7*2=147*5=35(7+5)*2=24 flipped =421435425*3=155*2=10(5+2)*3=21...flipped =12151012
y equals x-4 plus 2 is the same as y = x-2. You just translate the graph of y=x, 2 units to the right, OR 2 down.
x = 7 and 2/3
x+2=9 x=9-2 x=7
3x + 9 = 5x - 43x +13 = 5x13 = 2x13/2 = xso x = 6.5
2x13
2
X=2
x=27
x = -2
9 plus 7 equals 144. Generally, x plus y = x(x+y).
X=4.2666666666667
(x+2)/(x+2) = 1x equals infinity
x = 14
So 4x + 2 = 2. x = 0
x=7 3/4